Content Creators Above Sixty: A qualitative analyses on the ageing discourse by older adults on TikTok - Gradwohl, Regina; Pauló, Edit (Magyar Gerontológia, 2024)
Platforms of social media and online memes often paint a similar picture about older adults: technophobes, who cannot keep up with the vastly changing world of the internet. Despite this, the number of older internet users grows rapidly, even on platforms associated with the younger generations, such as TikTok.